Application Of Leaflet Media In Learning Missouri Mathematics Project (Mmp) Model Against Independence of Student Mathematics - Irfa Oktavia Rostina; Nurma Izzati (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2020)
Learning independence is a condition where someone determines the decision on an initiative to solve learning problems through self-confidence. This study aims to determine the independence of student learning, determine the response of leaflet media in MMP learning, and determine the effect of leaflet media in MMP learning on student learning independence. The research method uses a pseudo experimental design. The study population was the X class Islamic Center in the city of Cirebon and samples were taken based on purposive sampling technique that is obtained class X AKL2. The research instrument used was a questionnaire with descriptive data analysis techniques and simple regression analysis. The results showed an average score of learning independence was 67.133, the average value of leaflet media response scores in MMP learning was 82.86, and the influence of media leaflets on learning independence was 50,4% with a regression equation ????=62,185 + 0,084X.